Oral Surgical Site Infections and Wound Healing Associated with Silk Fibroin Sutures versus Alternative Suture Materials: A Systematic Review - Kranti Kiran Reddy Ealla; Neema Kumari; Ellojita Rout; Vikas Sahu; Vishnu Priya Veeraraghavan; Pratibha Ramani (Journal of Clinical and Diagnostic Research)
Introduction: Delayed or improper wound healing can lead to Surgical Site Infections (SSIs), which are associated with increased mortality, morbidity, readmission rates and healthcare costs. Dental sutures are routinely used to close wounds, promote haemostasis and prevent infection. Although non absorbable sutures are preferred for promoting wound healing and preventing infection, Silk Fibroin (SF) sutures are still used due to their affordability and favourable properties. However, their multifilament structure makes them susceptible to higher bacterial adherence. Aim: To compare the effectiveness of SF sutures in reducing SSIs and promoting wound healing with other suture materials used in dental procedures. Materials and Methods: A systematic review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) 2020 checklist. PubMed, University of Toronto libraries and the Web of Science (WoS) were searched using specific keywords until January 4, 2025. Data were extracted and a risk of bias assessment was performed using the Risk of Bias 2 (RoB 2) and Risk of Bias In Non randomised Studies - of Interventions (ROBINS-I) tools. Nine studies were included. Results: The study demonstrated that non resorbable multifilament SF sutures show high microbial adherence and prolonged wound closure time compared to other materials, due to their multifilament and braided structure. However, significant infections were rarely reported. Results regarding bleeding, pain and swelling varied across studies and were mostly non significant on day 7. Conclusion: Antiseptic or antibiotic coatings on SF sutures can reduce bacterial adherence and lower the risk of infection, especially given their significantly higher adherence compared to other sutures.